Pendekatan Konseling Feminis dalam Menumbuhkan Kesadaran Peserta Didik Mengenai Kesetaraan Gender di SMA - Hakim, Moch. Lukman; Holidy, Moch. Faisol; Pratama, Dany Wahyu (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
This study aims to raise students awareness of gender equality in senior high schools. This research uses a literature study. The literature study method is an activity of collecting library data, reading, taking notes, and managing research materials. The subjects in this study were high school students. This study concludes that the use of providing counseling services with a feminist approach can increase students' awareness and understanding of gender equality so that they can respect one another. The conclusion of this study is evident from the results of research by previous researchers.